2013
DOI: 10.1177/1474515113487464
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tailored telemonitoring on heart failure patients’ knowledge, self-care, self-efficacy and adherence: A randomized controlled trial

Abstract: Tailored telemonitoring was found to educate patients with HF and to improve their self-care abilities and sense of self-efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
149
1
16

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(172 citation statements)
references
References 38 publications
(47 reference statements)
6
149
1
16
Order By: Relevance
“…The significant improvement of knowledge and self-efficacy in the PCE group in the present study supports Boyne et al [25], who found a telephone follow-up intervention to be effective at creating positive changes in self-care abilities and self-efficacy among patients with heart failure. However, an automatic telecare approach for chronic heart failure patients to improve and empower them to take care of their illness.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The significant improvement of knowledge and self-efficacy in the PCE group in the present study supports Boyne et al [25], who found a telephone follow-up intervention to be effective at creating positive changes in self-care abilities and self-efficacy among patients with heart failure. However, an automatic telecare approach for chronic heart failure patients to improve and empower them to take care of their illness.…”
Section: Discussionsupporting
confidence: 79%
“…Video-based CPR self-education with a manikin was effective in the control group. However, the PCE group with an interactive nursing instructor showed statistically monitoring device with a preset program was used in the study conducted by Boyne et al [25], whereas nurse-led telephone follow-up was used in the present study.…”
Section: Wwwkanorkrmentioning
confidence: 99%
“…Care of HF patients would significantly improve by implementing frequent NTproBNP monitoring in the home care setting and in increased telemonitoring of HF patients [14]. A research project aimed to implement BNP monitoring in the home (the HABIT trial) showed that patients can be taught to take their own blood for testing [4].…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy has been commonly addressed as a factor that influences the individual's engagement with medical treatment (e.g., Williams and Manias 2014;Corless et al 2012;Snell and White 2011;Cameron et al 2010;Boyne et al 2014). Self-efficacy refers to an individual's capacity to execute behaviors necessary to the specific situation (Bandura 1977).…”
Section: Cognitive Processesmentioning
confidence: 99%